2020
DOI: 10.1001/jamanetworkopen.2020.13880
|View full text |Cite
|
Sign up to set email alerts
|

Association of Nonsteroidal Anti-inflammatory Drug Use and Adverse Outcomes Among Patients Hospitalized With Influenza

Abstract: IMPORTANCE During the ongoing coronavirus disease 2019 pandemic, case reports have suggested that the use of nonsteroidal anti-inflammatory drugs (NSAIDs) may lead to adverse outcomes. OBJECTIVE To study the association of NSAID use with adverse outcomes in patients hospitalized with influenza or influenza pneumonia. DESIGN, SETTING, AND PARTICIPANTS This cohort study used propensity score matching among 7747 individuals aged 40 years or older who were hospitalized with influenza, confirmed by polymerase chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 31 publications
3
21
0
Order By: Relevance
“…Third, the adverse effects of NSAIDs on the course of pneumonia may be specific to bacterial infections. A recent study on the risk of adverse outcomes in users of NSAIDs hospitalized for influenza found no association between use of NSAIDs and ICU admission or death [9], similar to the findings in this study.…”
Section: Findings In Relation To Other Studiessupporting
confidence: 89%
See 2 more Smart Citations
“…Third, the adverse effects of NSAIDs on the course of pneumonia may be specific to bacterial infections. A recent study on the risk of adverse outcomes in users of NSAIDs hospitalized for influenza found no association between use of NSAIDs and ICU admission or death [9], similar to the findings in this study.…”
Section: Findings In Relation To Other Studiessupporting
confidence: 89%
“…Ideally, confounding by indication would be mitigated using an active comparator; however, a suitable active comparator does not exist for ibuprofen. In a previous study, users of paracetamol differed more from NSAID users than did non-users of NSAIDs [9].…”
Section: Plos Medicinementioning
confidence: 78%
See 1 more Smart Citation
“…The available evidence stems mainly from studies on community acquired bacterial pneumonia and show that use of NSAIDs is associated with bacterial complications, specifically empyema and lung abscesses (4)(5)(6)(7). For viral illness, use of NSAIDs was not associated with mortality in ICU patients with influenza H1N1 during the 2009 pandemic (8), and a recent study found that use of NSAIDs was not associated with mortality in patients hospitalized for influenza (9). As use of ibuprofen and other NSAIDs is widespread, data on its safety is urgently needed to guide clinicians and patients on how to use NSAIDs during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…But, taken together, along with the pharmacovigilance cases, the experimental studies and the pharmacological plausibility, we do believe that all these complementary data constitute a solid range of converging clinical and scientific evidence supporting an increased risk of severe bacterial complications under NSAIDs. Moreover, Pottegard et al have also recently observed in a nationwide population-based cohort study of patients with confirmed influenza or influenza-related pneumonia, an increased risk of pleuro-pulmonary complications for NSAID users [4] .…”
Section: Abbreviationsmentioning
confidence: 91%